Telaah Segitiga Retorika Aristoteles dalam Video Ceramah Digital - Mohammad Wildan Esra; Aang Ridwan; Umi Halwati (KOMUNIKA, 2026)
The development of digital media has transformed the landscape of Islamic preaching, where religious communicators now deliver messages through platforms such as YouTube. This phenomenon demands persuasive and adaptive communication skills to compete amid information overload. This study aims to analyze the actualization characteristics of ethos, pathos, and logos elements in the digital lectures of Ustadz Muhammad Nuzul Dzikri based on Aristotle's Rhetorical Triangle theory. A qualitative content analysis method with a constructivism paradigm was employed. The data source is a lecture video entitled "DUA RASA YANG HARUS ADA | Riyadhus Shalihin" on the YouTube channel Muhammad Nuzul Dzikri. Data were collected through audiovisual observation and documentation, then coded according to ethos, pathos, and logos categories. The findings reveal that ethos is constructed through Islamic opening rituals, Qur'anic and hadith citations, and references to authoritative scholars. Pathos is actualized through humanitarian prayers, appreciative expressions, validation of spiritual vulnerability, and tragic narratives about despair. Logos is applied through empirical analogies such as bird's wings, medicine dosage, and student experiences to abstract theological concepts. The conclusion is that Ustadz Muhammad Nuzul Dzikri's digital lectures implement Aristotle's rhetorical trilogy in a structured and proportional manner, producing effective, rational, and emotionally resonant da'wah communication for urban audiences.